Epidemiology and genetic risk factors of suicidal behaviour in South Africa - Kootbodien, Tahira (Department of Pathology, 2024)
Background: Suicide is an urgent public health problem. Fatal suicidal behaviour (individuals who died by suicide) and non-fatal suicidal behaviour (attempted suicide, self-harm, and suicidal ideation) comprise a complex interplay of individual, social, environmental, and biological factors, that are not fully understood. Given the considerable societal cost associated with suicide and health inequality in South Africa, there is a critical need to determine the burden of suicide and risk factors associated with suicide, to understand who is most at risk to inform effective prevention efforts. Despite clear evidence of multiple risk factors, suicidal behaviour remains difficult to predict and prevent. Prevention efforts in South Africa may be limited by the lack of a national suicide prevention plan and the low base rate of individuals who died by suicide may impede research comparing fatal and non-fatal suicidal behaviour in settings such as ours. In addition, existing suicide data are derived primarily from high-income countries rather than lowand middle-income countries (LMICs) where suicide and poverty levels are high, and the mental health treatment gap is large. The purpose of this study was to broaden our understanding of suicidal behaviour in South Africa by combining various data sources, each representing a unique perspective of the problem, to build on existing knowledge that may inform suicide prevention strategies in South Africa. This thesis is organised into four studies and aimed to investigate risk factors associated with suicidal behaviour and to identify opportunities for targeted suicide prevention. The specific objectives of each study component were as follows: • To describe trends and demographic risk factors in deaths from suicide as well as other conditions that may include suicide to identify populations at risk in South Africa (Study 1). • To investigate the association between environmental and occupational organophosphate pesticide (OP) exposure and attempted suicide in adults admitted to hospital in Cape Town, South Africa (Study 2). • To explore the genetic architecture underlying suicidal behaviour and psychiatric disorders to understand the genetic factors that increase the risk of suicidal behaviour (Study 3). • To describe healthcare utilisation 12 months before suicidal behaviour among individuals who attempted suicide and who died by suicide, to identify opportunities for prevention in Cape Town, South Africa (Study 4). Methods: This thesis included an ecological time-series study of national suicide mortality data from Statistics South Africa using joinpoint regression analysis (Study 1, N=10.3 million recorded deaths from 1997 to 2016; 8,573 deaths from suicide); a conditional logistic regression analysis of an attempted suicide hospital-based case-control study (Study 2, N=400; 200 cases and controls); a genome-wide genetic correlation study of suicidal ideation, self-harm, attempted and fatal suicide (samples [n] ranged from 62,648 to 125,844), and selected psychiatric disorders (n ranged from 9,954 to 386,533) using a genomic structural equation modelling approach (Study 3); and a retrospective cohort of linked electronic health records of individuals who attempted suicide and were admitted to hospital and a case series of fatal suicides on whom forensic autopsies were performed at a mortuary in Cape Town (Study 4, N=484). Results: The key findings in this study show that (i) suicide mortality rates were consistently higher in men than women between 1997 and 2016 (Study 1). Suicide rates increased by 7.7% among young people aged 15 to 29 years. Hanging, poisoning and firearms were the most frequent methods of suicide used. Subgroup analysis showed suicide by hanging and poisoning mortality rates increased by 2.9% and 3.7% across 20 years. Suicide deaths were underreported and may be included among deaths by accidental injuries and undetermined intent. However, these patterns varied by method of death (hanging, poisoning and firearm injury) over the study period. The largest proportion of suicide deaths may be potentially misclassified as accidental hanging and hanging by undetermined intent, and to a lesser extent, accidental poisoning and poisoning by undetermined intent. In contrast, firearm-related deaths were more likely to indicate a homicide than a suicide death. Missing data on select sociodemographic variables limited the accuracy and generalisability of our findings. (ii) Pesticide use in homes and gardens was common (85%); however, there was no association between attempted suicide and environmental (household, garden, and occupational) OP exposure (Study 2). Hazardous drinking and unemployment with no household income were significantly associated with an increased risk of attempted suicide while sharing the house with more than three persons was protective. (iii) We observed strong significant genetic correlations (rg) between suicidal ideation, attempted suicide, and self-harm (rg range, 0.71 to 1.09) and moderate-to-strong genetic correlations between suicidal behaviour traits and a range of psychiatric disorders (Study 3). The strongest genetic correlation was noted for major depressive disorder and suicidal ideation (Ever contemplated self-harm, rg=0.86±0.07, p=1.62x10-36). Multivariate genomic analysis revealed a single (common) factor structure for suicidal behaviour traits, major depressive disorder, attention-deficit hyperactivity disorder (ADHD), and alcohol use disorder. Approximately 2,951 genes and 98 sub-network hub genes were associated with the common factor, and shared biological pathways include involvement in developmental biology, signal transduction and RNA degradation. (iv) Approximately two-thirds of cases had at least one prior visit to a health care facility in the 12 months leading to suicidal behaviour (Study 4). The prevalence of psychiatric disorders was lower for individuals who died by suicide than attempted suicides but both groups interacted equally (approximately 65%) with the healthcare system during the 12 months leading to suicidal behaviour. Patients who used primary care services in the year before dying by suicide attended for the management of their chronic conditions (such as cardiovascular disease and diabetes) and emergency medical care for assault-related injuries. For attempted suicides, common reasons for a healthcare visit were for management of their chronic condition, HIV care, and a psychiatric diagnosis of depression, bipolar, or substance use disorders. Conclusions: This study expands on previous research and shows that while common risk factors are shared by individuals with fatal and non-fatal suicidal behaviour, the degree of risk varies across suicide groups, age, and sex. Findings of increased genetic risk of suicidal behaviour among individuals with psychiatric disorders suggest that identification and early treatment of co-morbid psychiatric disorders (major depression, alcohol use disorder, ADHD, and schizophrenia) should be included in suicide prevention strategies. Evidence of potential misclassification of suicide death within accidental injuries and undetermined intent categories may explain the underestimation of suicide mortality reported in this study. Combined with the high proportion of missing data in the national vital statistics and poor data quality of external causes of death, these findings suggest a critical need for ongoing training on the cause of death certification and further interventions to improve suicide data quality. Further, continued monitoring of suicide mortality data and linking electronic health records may provide opportunities for suicide surveillance that can help identify where prevention strategies should be allocated for maximum benefit, such as primary healthcare outpatient facilities, emergency treatment centres, and antiretroviral clinics.